Employee Engagement In Organizations: A Study Done On The Operational Employees Of The 5-Star Hotels In Kolkata (PUSA Journal of Hospitality and Applied Sciences, 2022)
Background: Employee engagement is one of the most recent areas of research in management. It is the basis for any  organization’s success. The engaged workforce shows its physical and mental commitment, generates energy on the  roles to be performed, and gives productivity to a maximum extent which helps in achieving overall business goals.  Objective: The major objective of this study was to determine the level of employee engagement of the operational staff.  Methodology: The questionnaire was prepared to test the knowledge, employee engagement levels, and organizational  culture levels of the employees. Responses were recorded via the online medium from 100 samples (50 males and 50  females), the majority of them were in the age group of 20 to 25 years and were operational employees of 5-star hotels  in Kolkata. A 5-point Likert scale was used. Result: The average knowledge score of the sample was 5.45, which  indicated great awareness of the concept. The sample achieved an average score of 39.92 in employee engagement,  24.2 in job involvement, 40.59 in empowerment, and 24.78 in cognition, all of which were in the ‘high’ range. The  average organizational culture score achieved by the sample was 89.57. Pearson’s correlation coefficient was calculated  for the two variables, employee engagement, and organizational culture, and the correlation coefficient was, 0.534  among males and 0.569 among females. The values of the correlation coefficient indicated a positive correlation among  the variables. Conclusion: The findings of this study contributed to the knowledge and understanding of the selected  factors, which leads to a better understanding of organizational practices that will lead to employee engagement.
Keywords: Engaged Employee; Organizational Culture; Job Involvement; Empowerment; Hospitality Sector